Knowledge of Lassa Fever and Its Determinants among Traders in Izzi Community in South-East Nigeria - E. U. Nwonwu; C. Alo; A. F. Una; U. C. Madubueze; I. Eze; N. C. Eze; L. U. Ogbonnaya; I. C. Akamike (Archives of Current Research International, 2018)
Background: Lassa fever is a viral hemorrhagic fever found predominantly in West Africa with the potential to cause approximately 5,000 deaths per year. However, good knowledge of the disease may reduce the infection rate. The study assessed the knowledge of Lassa fever and its determinants among traders in Izzi community Ebonyi State, Nigeria. Methods: A descriptive cross-sectional study was conducted among 248 traders selected by simple random sampling method. Data were collected from respondents who gave their informed consent using interviewer-administered semi-structured questionnaire and analyzed using Chi-square test (Fisher’s exact test where appropriate) for categorical variables and binary logistic regression for predictors of the outcome variables. Statistical significance was set at p < 0.05 Results: Most of the respondents (40%) were within the age group of 21 – 30 years. Majority of the traders were females (64.1%), married (64.1%) and predominantly Christians (97.2%). A large proportion of the respondents (43.1%) had secondary education level, and 10.1% had no formal education. Awareness of Lassa fever was high 197 (79.4%) among the traders. The commonest source of information was radio 152 (61.3%), and only 15% of the respondents heard about Lassa fever from health workers. Overall knowledge of Lassa fever was poor: 173 (70%) of the traders had poor knowledge, and only 53 (21.4%) had excellent knowledge. Majority of the traders 160 (64.5%) ate rat’s meat. Factors found to be significantly associated with knowledge of Lassa fever include gender, educational status, and consumption of rat. Predictors of adequate knowledge include male gender and completing tertiary education. Conclusion: The high level of awareness of Lassa fever in this study did not translate to adequate knowledge of the disease. The poor level of knowledge points towards a growing need to step up not just awareness of Lassa fever but also in-depth knowledge of the causes, mode of transmission and prevention of the disease through public education with special access to the female cohort.